Determinan Minat Menjadi Guru pada Mahasiswa Pendidikan Ekonomi (Literatur Review) - Dyah Ayu Margiati; Amir Mahmud (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to Analyze and syntesize the determinants influencing education student’s interest in pursuing a teaching career through a literature review approach. The teaching profession, as stipulated in Law Number 14 of 2005 concerning teacher and Lecturers, holds a strategic position in the national education system; however, not all education students demonstrate a career orientation aligned with this profession. This study employed a literature review method by analyzing 20 scientific articles published within the last ten years retrieved from google scholar using the keywords “interest in becoming a teacher”, “teacher readiness”, and “career choice”. The findings indicate that student’s interest in becoming teacher rangers from moderate to high and is influenced by multidimensional interactions among internal factor (self-efficacy, motivation, perceptions of the teaching professions, locus of control), social factors (family and peer support), and academic as well as professional experiences (teaching practicum, microteaching, professional teacher education programs, and kampus mengajar). Self-efficacy and family support emerged as the most consistent determinants, either directly or through mediating mechanisms. These findings suggest that enhancing student’s interest in the teaching profession requires comprehensive strategies integrating psychological reinforcement, meaningful practical experiences, and supportive social environments within teacher education institutions.